Bidirectional Association Between COVID-19 and Mental Health Disorders: A Narrative Review - Haleh Talaie (Shaheed Beheshti University of Medical Sciences, 2021)
Background: Fear, anxiety, and stress are natural reactions of the human body to unpredictable and potentially threatening conditions. Currently, individuals are encountering Coronavirus Disease 2019 (COVID-19) pandemic; it is caused by a virulent, partially unknown pathogen with high transmissibility, recognized as Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It is conceivable to experience anxiety, stress, and subsequent mental health disorders during the pandemic. This narrative review provided a brief overview of mechanisms involved in COVID-19 and mental health disorders as well as the bidirectional association between them. Methods: Scientific electronic databases, such as PubMed, Scopus, Web of Science, and Google Scholar were thoroughly searched, based on different keywords in this study. Results: Lifestyle changes and isolation for breaking the chain of infection facilitate mental health disorders development more than before. Since the onset of the pandemic, the prevalence of mental health disorders has significantly increased. Moreover, studies suggested that the incidence of COVID-19 and the progression of the disease to a severe and life-threatening stage is higher in individuals with a history of mental health disorders. Inflammation is caused by, also may cause mental health disorders. Besides, COVID-19 is associated with cytokine storm and subsequent inflammation. Conclusion: There seems to be a bidirectional association between COVID-19 and mental health disorders, in which inflammation acts as an adaptor.